2019
DOI: 10.3389/fevo.2019.00205
|View full text |Cite
|
Sign up to set email alerts
|

Drilling Down Hotspots of Intraspecific Diversity to Bring Them Into On-Ground Conservation of Threatened Species

Abstract: Unprecedented rates of biodiversity loss raise the urgency for preserving species ability to cope with ongoing global changes. An approach in this direction is to target intra-specific hotspots of genetic diversity as conservation priorities. However, these hotspots are often identified by sampling at a spatial resolution too coarse to be useful in practical management of threatened species, hindering the long-appealed dialog between conservation stakeholders and conservation genetic researchers. Here, we inve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…It is worth noting that the unavailability of exact locations from previous surveys does not allow for direct comparison and inferences on population trends. However, we visited 26 known historical sites for B. pachypus (see Zampiglia et al 2019) and in 14 of them (54%), the presence of the species was not confirmed. A negative trend was also reported by local people (shepherds, farmers, woodcutters, and walkers), who confirmed that B. pachypus is less widespread now compared to the early 1990s when it was ubiquitous and abundant in hilly and mountain streams and ponds, as well as in artificial aquatic environments used for agriculture and local pastoralism.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…It is worth noting that the unavailability of exact locations from previous surveys does not allow for direct comparison and inferences on population trends. However, we visited 26 known historical sites for B. pachypus (see Zampiglia et al 2019) and in 14 of them (54%), the presence of the species was not confirmed. A negative trend was also reported by local people (shepherds, farmers, woodcutters, and walkers), who confirmed that B. pachypus is less widespread now compared to the early 1990s when it was ubiquitous and abundant in hilly and mountain streams and ponds, as well as in artificial aquatic environments used for agriculture and local pastoralism.…”
Section: Discussionmentioning
confidence: 96%
“…Climatic and orographic diversification have generated ecological gradients and highly heterogeneous vegetation typologies (Spampinato et al 2008). In endemism, relict species, and ancient woods, the Aspromonte represents a hotspot of plant and animal biodiversity at the species, genetic, and community levels (Spampinato et al 2008;Zampiglia et al 2019;Piovesan et al 2020). Biodiversity conservation within the Aspromonte region is undertaken by the Aspromonte National Park (ANP), together with 57 Natura 2000 areas, 55 of which are Special Areas of Conservation (SACs) and two are Special Protection Areas (SPAs).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…We collected adult males from close but distinct ponds to ensure similar environmental conditions and predators, and to avoid collecting related individuals. Also, we selected this population because it has not been affected by either recent and historical decline, and all the individuals can be considered belonging to a unique and panmittic population [29]. Details about the study species, sampling and housing procedures are provided as Supplementary material.…”
Section: Methodsmentioning
confidence: 99%
“…In this scenario, hotspots are 'melting pots' generated by (a) localized contraction and divergence of these populations and (b) subsequent admixture during re-expansion (Canestrelli et al, 2010). Under this model, priority areas for conservation might exist within the broader refugia; however, the spatial resolution of many phylogeographic studies is too coarse to pinpoint these areas and allow targeted allocation of resources (Zampiglia et al, 2019).…”
Section: Introductionmentioning
confidence: 99%